COPING WITH CATASTROPHES: EARTHQUAKES, BENEFACTORS, AND ARCHIEREI S IN LYCIA IN THE EARLY 2ND CENTURY CE. - Lepke, Andrew (Hesperia)
This article examines the evidence for seismic activity in Lycia during the early 2nd century ce. By comparing a hitherto neglected passage in the Chronographia of John Malalas with the epigraphic evidence from Patara and other Lycian cities, it reevaluates the chronology of major earthquakes in Lycia and suggests that a destructive event in 115 ce preceded the catastrophe of 141/2 ce. Using recently published inscriptions and a new text presented here for the first time, the study sheds light on the way in which natural disasters influenced urban development, and on the role played by civic benefactors in the region's recovery.